2021
DOI: 10.1186/s12906-020-03195-w
|View full text |Cite
|
Sign up to set email alerts
|

Ethanolic extract of Nymphaea lotus L. (Nymphaeaceae) leaves exhibits in vitro antioxidant, in vivo anti-inflammatory and cytotoxic activities on Jurkat and MCF-7 cancer cell lines

Abstract: Background Nymphaea lotus L. (N. lotus) is an aquatic plant with anecdotal reports suggesting its use in the traditional management of cancer. However, there is a paucity of data on the antioxidant, anti-inflammatory and cytotoxic properties of N. lotus in relation to its phytochemical and elemental contents. This study aimed at determining the antioxidant, anti-inflammatory and cytotoxic properties of the hydro-ethanolic extract of N. lotus leaves (NLE), and its phenolic, flavonoid and element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…In line with our results, cancer cells of the types HeLa, MCF-7, Hep3B, A549, C6, and HT29 were found to be sensitive to the cytotoxicity of a methanolic extract of four cyanobacteria ( Chroococus minutus , Geitlerinema carotinosum , Nostoc linckia , and Anabaena oryzae ) rich in pigments and phenolics [ 138 ]. Our findings are consistent with those of Kim et al [ 139 ], Mesas et al [ 140 ], and N’guessan et al [ 141 ], who all found that ethanolic extracts of medicinal plants exhibited comparable cytotoxicity toward human cancer cells (T84, HT1080, MCF-7, MDA-MB231, and HCT-15). They also proposed that the presence of chlorophyll, carotenoids, and phenolics in the extract could be associated with the antioxidant and anticancer effects that these compounds possess.…”
Section: Resultssupporting
confidence: 93%
“…In line with our results, cancer cells of the types HeLa, MCF-7, Hep3B, A549, C6, and HT29 were found to be sensitive to the cytotoxicity of a methanolic extract of four cyanobacteria ( Chroococus minutus , Geitlerinema carotinosum , Nostoc linckia , and Anabaena oryzae ) rich in pigments and phenolics [ 138 ]. Our findings are consistent with those of Kim et al [ 139 ], Mesas et al [ 140 ], and N’guessan et al [ 141 ], who all found that ethanolic extracts of medicinal plants exhibited comparable cytotoxicity toward human cancer cells (T84, HT1080, MCF-7, MDA-MB231, and HCT-15). They also proposed that the presence of chlorophyll, carotenoids, and phenolics in the extract could be associated with the antioxidant and anticancer effects that these compounds possess.…”
Section: Resultssupporting
confidence: 93%
“…of 100-250-500 mg/kg, with diclofenac and hydrocortisone (as positive controls) by paw oedema and skin prick tests in carrageenan-induced Sprague-Dawley rats. It was found that paw oedema sizes decrease in a dose-dependent manner thus supporting that it might contain some anti-inflammatory compounds causing the inhibition of the prostaglandin-induced inflammatory pathway [53]. The N. hybrida ethanol extract (NHE) inhibits the LPS-associated inflammatory response by blocking the activation of NF-κB and MAPK pathways in RAW264.7 cells and effectively alleviating the inflammatory response of acute inflammation [54].…”
Section: In Vitro and In Vivo Anti-inflammatory Activity The Anti-inflammatory Activity Of Ethanolic Extracts Ofmentioning
confidence: 98%
“…Their combination is based on the traditional Chinese medicine weight loss theory of tonifying qi and invigorating the spleen, dispelling dampness and resolving phlegm [ 12 ]. Ginseng [ 13 ], lotus leaf [ 14 ], poria cocos [ 15 ], tangerine peel [ 16 ], rice bean [ 17 ] and cassia [ 18 ] all have antioxidant and anti-inflammatory properties and are commonly used as food or dietary supplements for weight loss in China, Korea and other eastern countries.…”
Section: Introductionmentioning
confidence: 99%